Implementation of the Heronion mean (HeM) in the predictor corrector mode. Issue 7 (3rd October 2021) - Jasim, Mahmood D.
Abstract: As is known, one of the most important and famous methods for solving initial value problems are the Runge Kutta methods. As the results of developing the computers and processors, now some of the old methods become not appropriate with parallel computers, so, here we introduce a new method suitable for the current generations of computers.